Organizational Integration and Collaborative Medical Practices in Infection and Bacterial Control: A Systematic Review - AL-Salem, Hadi Mohammed Saleh; ALGhamdi, Abdullah Nasser Mohammed Abdullah; Alalhareth, Mohammed Ali Mushabbab; Asiri, Fatimah Hassan Mohammad; Qumaish, Awatif Faisal Nasser Bin; Algarni, Jaber Mohammad Ahmad; Al Shafi, Albandari Mohammed Abdullah (Journal of Posthumanism, 2024)
Background: Healthcare-associated infections (HAIs) and bacterial transmission remain major challenges to patient safety and healthcare quality worldwide. Traditional infection control efforts that operate within isolated clinical departments often fail to address the complex, system-wide factors contributing to infection spread. Increasing attention has therefore been directed toward organizational integration and collaborative medical practices as effective strategies for improving infection prevention and control. Objective: This systematic review aims to examine the impact of organizational integration and interprofessional collaboration on reducing infection and bacterial transmission within healthcare settings. Methods: A systematic search was conducted across major electronic databases, including PubMed, Scopus, Web of Science, CINAHL, and the Cochrane Library, for peer-reviewed studies published between 2016 and 2024. Studies were selected according to predefined inclusion criteria and screened following PRISMA 2020 guidelines. Data were extracted and synthesized thematically, with quality appraisal performed using standardized assessment tools. Results: The review identified consistent evidence that integrated governance structures, shared infection control protocols, multidisciplinary teamwork, and coordinated surveillance systems are associated with reduced HAIs, improved compliance with infection prevention measures, and enhanced antimicrobial stewardship. Conclusion: Organizational integration and collaborative medical practices play a critical role in strengthening infection and bacterial control. System-level approaches that promote coordination, shared accountability, and continuous communication are essential for sustainable infection prevention in modern healthcare systems.